Randomised clinical trial: standard of care versus early‐transjugular intrahepatic porto‐systemic shunt (TIPSS) in patients with cirrhosis and oesophageal variceal bleeding. Issue 1 (26th May 2020) - Dunne, Philip D. J.; Sinha, Rohit; Stanley, Adrian J.; Lachlan, Neil; Ireland, Hamish; Shams, Aman; Kasthuri, Ram; Forrest, Ewan H.; Hayes, Peter C.
Summary: Background: Early‐transjugular intrahepatic porto‐systemic shunt (TIPSS) has been recommended in international guidelines for high‐risk patients with oesophageal variceal bleeding. Aim: To validate the results of a previous randomised control trial which supports use of early‐TIPSS. Methods: In a two‐centre open‐label parallel‐group randomised control trial, patients with cirrhosis and acute variceal bleeding were recruited following haemostasis with vaso‐active drugs and endoscopic band ligation. Participants were randomised to standard of care or early‐TIPSS. The primary outcome was 1‐year survival, secondary outcomes included early and late rebleeding, and complications of portal hypertension. Results: Fifty‐eight patients (58 ± 11.12 years; 32.7% female) were randomised. After one year, seven patients died in the standard of care group and six in the early‐TIPSS group, a 1‐year survival of 75.9% vs 79.3% respectively ( P  = 0.79). Variceal rebleeding occurred in eight patients in the standard of care group compared with three patients in the early‐TIPSS group ( P  = 0.09). Not all participants randomised to early‐TIPSS received the intervention in time. For those receiving TIPSS per‐protocol, variceal rebleeding rates were reduced (0% vs 27.6%, P  = 0.04) but this had no effect on survival (76.9% vs 75.9%, P  = 0.91). Serious adverse events were similar in both treatment groups, except that rates of hepatic encephalopathy were higher in patients receiving TIPSS (46.1% vs 20.7%, P  < 0.05). Conclusions: Early‐TIPSS reduced variceal rebleeding, increased encephalopathy but had no effect on survival in high‐risk patients with oesophageal variceal bleeding. Early‐TIPSS may not be feasible in many centres however, larger studies are needed. ClinicalTrials.gov reference: NCT02377141.